Integrated Molar Chiral Sensing Based on High‑Q Metasurface - Chen, Yang; Zhao, Chen; Zhang, Yongzhe; Qiu, Cheng-wei (Nano letters, 2020)
Circular dichroism (CD) spectroscopy is conventionally utilized for the enantiomer-specific analysis of chiral samples, which is of great significance in academia and industry. Recently, metasurfaces have been introduced for enhancing the sensitivity of CD spectroscopy. However, the obtained CD spectrum alone cannot provide the enantiomer composition of a chiral sample. It should be normalized by the molar concentration of chiral molecules, which is usually measured on a different platform. Here, for the first time we demonstrate the integrated acquisition of CD spectrum and molar concentration over an individual metasurface with high sensitivities. High-Q resonances are supported on the metasurface, governed by bound states in the continuum. The generated superchiral field enables a 59-times enhancement of CD signal. Meanwhile, the refractive index-based detection of molar concentration achieves a large figure-of-merit of 80.6. Accordingly, a standard procedure is established for the integrated molar chiral sensing with high sensitivity.